(untitled) (Research, Society and Development, 2021)
This work, based on a bibliographical review, discusses the role of work, education and professional and technological education in human development. Human beings have work as a defining element of their formation and constitution, in such a way that all social relationships are/are conditioned to it, including education influenced by market interests, especially public ones. Federal Institutes also suffer from these influences, but they try to resist and offer an integrated education, having work as an educational principle with a view to omnilateral training capable of enabling students to ascend socially and become agents of change.